PENCEGAHAN KECANDUAN ALKOHOL PADA REMAJA MELALUI LAYANAN BIMBINGAN KELOMPOK BERBASIS TEKNIKSELF-MANAGEMENT - M Fadhli Aviv; Kusnadi; Zhila Jannati (CV. ADIBA AISHA AMIRA, 2023)
In helping to change the behavior of adolescents addicted to alcohol, they need mentors who guide them to get away from alcohol, switch to a good path, leave the conduct of intoxicating drinks, and focus on achieving the future. This thesis is entitled